Feasibility of qory 'aroby for class II salafiyah ula at bin baz islamic center - Amrin Mustofa; Suci Rafi Sari; Ahmad Mulalic (Yayasan Azhar Amanaa Yogyakarta, 2025)
The feasibility study of a textbook is highly important as it relates to the content it delivers. Developing an Arabic language textbook must take into account its foundational principles and pedagogical bases to ensure that the resulting material aligns with the needs of the learners. Specifically, the focus lies on whether the textbook meets the feasibility standards based on expert theories and how the content is structured and delivered through the concepts of selection, gradation, presentation, and repetition. Additionally, it is essential to evaluate the strengths and weaknesses of the Qory ‘Aroby textbook. This study is a qualitative research using the literature review method. The results show that the Arabic language textbook Qory ‘Aroby, used in the Salafiyah Class II at the Islamic Centre Bin Baz, aligns well with Mackey's theoretical framework, fulfilling the stages of selection, gradation, presentation, and repetition. However, in terms of presentation, some adjustments are still needed, such as the completeness of punctuation marks, the inclusion of a syllabus appendix, and the clarity of material delivery, which still requires intensive teacher assistance.